Measurements of temperature of CNC machine tool ball screw utilising IR method - Zapłata, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
In numerous papers it is proposed to use IR measurements of feed axis ball screw temperature distribution in order to compensate CNC machine tool thermal errors. The paper aims to validate reliability of the IR measurements in application to the feed axes ball screws. The identification of key factors influencing the accuracy of the IR measurements of ball screw temperature distribution has been conducted. A test-bench utilizing a ball screw assembly with built-in temperature sensors was introduced and the experimental data are presented along with conclusions.
Keywords: thermography; ball screws; CNC machine tools; thermal error